Jean-Paul Sartre and Jean-Luc Marion: For the Love of God - Vinolo, Stéphane (Journal for continental philosophy of religion, 2022)
Jean-Paul Sartre is not an influential author in the work of Jean-Luc Marion. Yet, as is the case for the phenomenology of givenness, Sartre thinks love in terms of God. However, for Marion, Sartre is exemplary of those authors who have remained prisoner to metaphysics and to thinking God as the causa sui. By comparing the Sartrean and Marionian conceptions of love, the author shows that both are based on radically different conceptions of divinity, demonstrating at the same time how the link between God and being determines human love.